Relevansi Hukum Islam terhadap Pernikahan Adat Masyarakat Mandailing di Desa Tanjung Julu - Ritonga, Raja; Dongoran, Irham (Shautuna: Jurnal Ilmiah Mahasiswa Perbandingan Mazhab, 2024)
The implementation of traditional marriages in the Mandailing community is still very strong today. Because for the Mandailing people, marriage is a procession carried out according to religion and custom. So, until now, marriage in the Mandailing community still follows the customs that have been carried out by the ancestors of the Mandailing community for a long time, even though they have joined the teachings of the Islamic religion which is strongly adhered to by the community. This research was conducted to determine the traditional marriage process in the Mandailing community and its relevance to Islamic law. This research is field research, namely using Tanjung Julu village in Mandailing as a research object. The approach taken is a normative legal approach. In collecting data, observation, interviews, documentation, and a literature study were carried out. Next, all data was analyzed descriptively. The results of the research explain that the traditional marriage practices carried out by the Mandailing community in Tanjung Julu village still take place according to customs that have been passed down from generation to generation. Starting from the process of manyapai boru (khitbah), patibal sere (determining the dowry), and horja (wedding procession). Furthermore, all stages carried out in the wedding procession are adjusted to State Law and Islamic Law, so it can be concluded that Islamic teachings are still very relevant in all processions carried out by the community and do not violate the Law and teachings of the Islamic religion.